Pengembangan Video Penelitian Kuantitatif dalam Meningkatkan Kemampuan Analisis Data Mahasiswa - Af’idah, Irma Nur; Afrida, Fira Nadliratul; Nuraini, Latifah (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2024)
This research aims to develop video tutorials on quantitative methods in correlation and regression analysis. This type of research is Research and Development (R&D) with the ADDIE approach, namely Analysis, Design, Development, Implementation and Evaluation. The results obtained in this research were that the design stage included material and appearance, the development stage was a continuation of the design stage, the implementation stage was carried out on 60 semester 5 students. Next, evaluate the results of the video tutorial based on suggestions and comments from media expert validators and material experts. The average feasibility test results obtained were 85.625% in the very feasible category. The resulting learning video is considered very feasible and effective in improving students' data analysis skills with an improvement score of 29, 47%.